Cauda Epididymis Spermatozoa: Cryopreservation and Utilization for Artificial Insemination and In Vitro Fertilization - Pamungkas, Fitra Aji (Indonesian Animal Sciences Society, 2012)
Genetic material either from animals of economical interest or from wildlife conservation can be lost anytime by unexpected death of the animal, low libido, or disorder at reproduction. In this case, an effort can be made occur to avoid the total lost of that genetic material by using an epididymis spermatozoa. Cauda epididymis spermatozoa generally motile, mature and can be used to fertilize oocytes as well as ejaculated spermatozoa. Some research indicated that cryopreservation of cauda epididymis spermatozoa for the purpose of artificial insemination and in vitro fertilization showed the ability to fertilize oocytes and produce offspring. Key words: Spermatozoa, cauda epididymis, artificial insemination, in vitro fertilization